171 Neurosurgical Utilization, Charges, and Reimbursement Following the Affordable Care Act: Trends from 2011 to 2019. (April 2023) - Hersh, Andrew; Dedrickson, Tara; Gong, Jung Ho; Jimenez, Adrian; Materi, Joshua; Veeravagu, Anand; Ratliff, John K.; Azad, Tej D.
Abstract : INTRODUCTION: An estimated fifty million Americans receive Medicare healthcare coverage, a number expected to increase with an aging population. Despite rising costs, prior studies have established a downward trend in Medicare reimbursement rates adjusted for inflation for commonly billed surgical procedures. However, it is unclear if these trends hold true across all neurosurgical procedures. METHODS: We review the yearly Physician/Supplier Procedure Summary datasets from the Centers for Medicare and Medicaid Services for all procedures billed by neurosurgeons to Medicare Part B between 2011 and 2019. Procedural coding was categorized into cranial, spine, vascular, peripheral nerve, and radiosurgery cases. Weighted averages for charges and reimbursements adjusted for inflation were calculated each year. The ratio of the weighted mean reimbursement to weighted mean charge was calculated as the reimbursement-to-charge ratio (RCR), representing the proportion of charges reimbursed by Medicare. RESULTS: Overall enrollment-adjusted utilization of neurosurgical procedures decreased by 12%, with utilization in the inpatient setting decreasing by 24%. However, we identified a large increase in procedures at ambulatory surgery centers (639%) and in the outpatient setting (80%). Over the study period, inflation-adjusted, weighted mean charges decreased by 4.0% while reimbursement decreased by 4.6%, resulting in a decrease in the RCR of 0.6%. Procedure groups that saw increases in reimbursement included anterior and posterior cervical spine surgery, cranial functional and epilepsy procedures, cranial pain procedures, and endovascular procedures. Ambulatory surgery centers saw the greatest increase in charges and reimbursements. CONCLUSIONS: Overall reimbursement declined over the study period; however, significant variations emerged across procedural categories. We further find a significant shift in utilization and reimbursement for neurosurgical procedures outside of inpatient care settings.